Evaluation of genetic damage in lymphocytes of male infertile patients using cytokinesis-block micronucleus assay (Funded Work) - AKILPPRIENKA BALACHANDRAN; ALEKHYA ASHOKAN; SHALAKA SUDHIR RAMGIR; VALSALA GOPALAKRISHNAN ABILASH (International Journal of Pharma and Bio Sciences, 2019)
In overall infertile cases, 20-30% of infertile couples suffer from male factor. The other remaining 20-30% is due to a combination of female and male factors. Male infertility is a complex multifactorial disease encompassing genetic as well as non-genetic factors. On a genetic level, chromosomal aberrations, microdeletions, etc contribute significantly to the severity of the condition but the extent to which the impact of genetic and molecular aberrations on fertility is still unclear. The purpose of this research is to evaluate the cytogenetic aspects associated with male infertility by using the technique, cytokinesis-block micronucleus cytome (CBMN) assay. CBMN assay is an extensive technique that is used to study the effect of genotoxins to produce DNA damages and instabilities. In the present study, the CBMN assay was conducted in a total of 21 fertile controls and 23 infertile patient samples to determine the comparison between their genetic instabilities and correlation with male infertility. In the CBMN assay score, the total number of aberrations found in patients was 10.12% when compared to controls (1.21%) and it was found to be significantly different. The assay showed a significant amount of DNA damage and DNA misrepair in the form of binucleated cells, multinucleated cells, micronuclei, bridges in binucleated and multinucleated cells in the patient samples. Hence, it was concluded that there could be a relation between DNA damage and infertility in males. Further studies have to be done to confirm the relation between the significance of damage seen and infertility.